2017
DOI: 10.1021/acs.orglett.7b02266
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt-Catalyzed Oxidant-Free Spirocycle Synthesis by Liberation of Hydrogen

Abstract: The first example of oxidant-free cobalt-catalyzed synthesis of five-membered spirocycles is reported from benzimidates and maleimides utilizing nitrobenzene as promoter. In contrast to previously known cobalt-catalyzed oxidative C-H functionalization reactions, this transformation occurs efficiently in the absence of oxidant and is accompanied by liberation of hydrogen. The spiro-lactams were readily achieved by the hydrolysis of as-prepared spirocyclic compounds. The Cp*Rh(III) catalyst shows poor reactivity. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(45 citation statements)
references
References 73 publications
(13 reference statements)
0
45
0
Order By: Relevance
“…Benzimidate, as a powerful traceless directing group, [6] has been frequently used for the synthesis of structurally diverse heterocycles through reacting with diverse coupling partners, [6] especially with different kinds of alkenes. [7] In 2016, Liu and co-workers demonstrated that ruthenium-catalyzed annulation of benzimidates and acrylates can construct the lactam derivatives (Scheme 1a). [7a] Later, Ackermann and coworkers reported the cascade CÀ H/NÀ H allylation of aryl imidates in the presence of low-cost cobalt(III) catalyst (Scheme 1b).…”
mentioning
confidence: 99%
“…Benzimidate, as a powerful traceless directing group, [6] has been frequently used for the synthesis of structurally diverse heterocycles through reacting with diverse coupling partners, [6] especially with different kinds of alkenes. [7] In 2016, Liu and co-workers demonstrated that ruthenium-catalyzed annulation of benzimidates and acrylates can construct the lactam derivatives (Scheme 1a). [7a] Later, Ackermann and coworkers reported the cascade CÀ H/NÀ H allylation of aryl imidates in the presence of low-cost cobalt(III) catalyst (Scheme 1b).…”
mentioning
confidence: 99%
“…(1)].T he quinones played ad ual role as both one carbon component for the annulation and oxidant. Very recently,acobalt-catalyzed [4+ +1] cyclization of benzimidates with maleimides was also reported by Zhang et al [123] [Scheme 77, Eq. (2)].I ntriguingly,t his transformation occursi nt he absence of oxidantw ith the liberation of hydrogen instead.…”
Section: With Alkenes or Allenesmentioning
confidence: 88%
“…In 2018, Zhang and his co‐workers have reported the synthesis of spirosuccinimide derivatives from benzimidates with maleimides in the presence of Cp*Co(CO)I 2 without having any auxiliary ligand . This methodology furnished spirosuccinimides in good to excellent yields without any silver oxidant and also liberates H 2 gas as a side product.…”
Section: Annulation Of Aromatics With Maleimidesmentioning
confidence: 99%